Total bilirubin and bilirubin-to-triglycerides ratio predict changes in glycated hemoglobin in healthy children - Puerto-Carranza, Elsa; Nuevo-Casals, Silvia; Roca-Portella, Berta; Mas-Parés, Berta; Gómez-Vilarrubla, Ariadna; Carreras-Badosa, Gemma; Niubó, Maria; Prats-Puig, Anna; de Zegher, Francis; Ibáñez, Lourdes; Bassols, Judit; López-Bermejo, Abel (Frontiers in Endocrinology, 2023)
The datasets generated and analyzed during the current study are available from the corresponding author on reasonable request.Although bilirubin and triglycerides are known to regulate insulin secretion and glucose uptake, its associations with metabolic markers in pediatric populations are not fully known. Therefore, we aimed to analyze associations between total bilirubin (TB) and the bilirubin-to-triglycerides ratio (BTR) with metabolic markers in 246 healthy prepubertal children of whom 142 (58%) were reevaluated 4 years later.Anthropometrics and laboratory parameters [TB and its fractions (direct and indirect bilirubin), triglycerides, glucose, insulin, HOMA-IR and glycated hemoglobin (HbA1c)] were assessed at both baseline and follow-up. Results showed independent and negative associations of TB and BTR with baseline and follow-up HbA1c, especially in those children within the highest age group. We propose that TB and BTR predict HbA1c changes over time in healthy children. Our results indicate that TB and BTR may be useful parameters in studies of glucose tolerance in healthy children.